Accurate analytical models of hot carrier degradation in nMOSFET and nFinFET considering saturation effect. (1st February 2023) - Li, Zheng-Kang; Wu, Zhao-Hui; Zhang, Xiao-Wen; Li, Bin; Lin, Xiao-Ling
Abstract: In this paper, models of hot carrier degradation (HCD) in nMOSFET and nFinFET, combined with the physical mechanism and reaction-diffusion framework and considering saturation effect, are proposed. The HCD data of different technology nodes of nMOSFET and nFinFET are used to verify the accuracy of the models. The results show that the prediction errors of device parameter degradation under different stress voltages are less than 10% for several types of short channel devices, which is better than the existing reported research results. Furthermore, the models have simple analytical expressions that allow them to not only be applied to device HCD prediction, but also be extended to circuit level HCD prediction tool more easily.